2001
DOI: 10.1111/j.1754-4505.2001.tb00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health profile in an institutionalized population of Italian adults with mental retardation

Abstract: The oral health of 219 residents with mental retardation living in a long-term-care institution near Milan was assessed. The dental and periodontal status, daily habits, oral hygiene, and oral mucosal status were evaluated. Of the sample, 179 (81.7%) were males. The mean age of the residents was 61.3 years, and the degree of cooperation was evaluated as good for 131 subjects (59.8%), fair for 79 (36.1%), and poor for nine (4.1%). The percentage of residents who were edentulous was 21.5% (47 subjects), of whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
1
28
0
3
Order By: Relevance
“…Most patients assessed in this study had good oral hygiene, regardless of how severe their disabilities were. These data are consistent with studies reporting that institutionalized patients had better oral health than non-institutionalized ones 15,17 .…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Most patients assessed in this study had good oral hygiene, regardless of how severe their disabilities were. These data are consistent with studies reporting that institutionalized patients had better oral health than non-institutionalized ones 15,17 .…”
Section: Resultssupporting
confidence: 82%
“…Besides patient-specific factors, these studies correlate this high prevalence of dental caries with patients' socioeconomic background as families are often socially and emotionally disadvantaged and hardly provided with education on health, increasing the odds for oral diseases among these patients 3,[12][13][14][15][16] . Most patients assessed in this study had good oral hygiene, regardless of how severe their disabilities were.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…艢rednia warto艣膰 liczby D 3 MFT oraz liczba z臋b贸w (z pr贸chnic膮, usuni臋tych i wype艂nionych) przed leczeniem w znieczuleniu og贸lnym z uwzgl臋dnieniem p艂ci, wieku, rozpoznania, miejsca zamieszkania, sprawowanej opieki i kolejno艣ci zabiegu Obserwacje w艂asne potwierdzaj膮, 偶e 艣rednia warto艣膰 D 3 MFT zwi臋ksza si臋 wraz z wiekiem badanych os贸b. Podobne wyniki bada艅 odnotowuj膮 autorzy w innych publikacjach [13,14,22] [16,21,26,27].…”
Section: Om贸wienieunclassified
“…Several researchers have found that 18 to 84% of children and adults with ID have untreated caries compared with 16 to 55% in the general population [Guillikson, 1969;Murray and McLeod, 1973;Kendall, 1991Kendall, , 1992Cumella et al, 2000]. Others have found evidence that individuals with ID were more likely to receive poor treatment for dental caries, such as tooth extractions rather than restorations for dental problems, compared with individuals in the general population [Butts, 1967;Svatun and Heloe, 1975;Nowak, 1984;Shaw et al, 1986;Whyman et al, 1995;Shapira et al, 1998;Pregliasco et al, 2001;Vazquez et al, 2002]. Nowak [1984], for example, examined the oral health of 3,622 disabled individuals aged 0 -16烯 years living in the community.…”
Section: Overall Prevalencementioning
confidence: 99%